2016
DOI: 10.1111/bdi.12362
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thickness in bipolar disorder: a systematic review

Abstract: This systematic review further supports a link between specific structural brain abnormalities and BD. Future studies should investigate cortical thickness with respect to at-risk populations to determine whether these neuropathologies develop before or after the onset of BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
121
5
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 108 publications
20
121
5
3
Order By: Relevance
“…35 Furthermore, longitudinal voxel-and tensor-based morphometric studies support an association between depressive episodes and frontal and temporal gray matter (GM) loss in BD 36,37 and MDD. 5 Although the mechanisms underlying the potential lateralization effects of BD remain unknown, genes involved in handedness and language lateralization were associated with depression and BD in a recent study. 14,36,37 Moreover, thinner left temporal cortices is one of the most consistent findings across cortical thickness studies in BD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Furthermore, longitudinal voxel-and tensor-based morphometric studies support an association between depressive episodes and frontal and temporal gray matter (GM) loss in BD 36,37 and MDD. 5 Although the mechanisms underlying the potential lateralization effects of BD remain unknown, genes involved in handedness and language lateralization were associated with depression and BD in a recent study. 14,36,37 Moreover, thinner left temporal cortices is one of the most consistent findings across cortical thickness studies in BD.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although the neural underpinnings of illness progression remain poorly understood, it has been suggested that mood episodes can cause lasting neurobiological alterations. 5,6 These cortical regions are believed to play central roles in processing and regulation of emotions. 5,6 These cortical regions are believed to play central roles in processing and regulation of emotions.…”
mentioning
confidence: 99%
“…[26][27][28] In adults, a recent systematic review of studies examining cortical thickness showed that BD was associated with cortical thinning, predominantly in the left anterior cingulate cortex, left superior temporal gyrus and bilateral PFC. 29 In contrast, a meta-analysis of studies examining regional volumes in adults concluded that, besides right lateral ventricular enlargement, no other regional volumes were significantly different in individuals with BD. 30 Overlapping findings between youth and adult cortical thickness studies, but mixed findings between youth and adult volumetric studies, suggest volume and cortical thickness may follow different neurodevelopmental trajectories.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies of BD patients reported subtle but widespread CT abnormalities and showed decreased CT in the left anterior cingulate/paracingulate, left superior temporal gyrus and prefrontal regions (Rimol et al, 2010, Rimol et al, 2012, Hanford et al, 2016). And several studies of MDD patients reported reduced CT in the medial orbitofrontal gyrus and pars opercularis (van Eijndhoven et al, 2013, Tu et al, 2012), and a study reported increased CT in similar regions (Qiu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%